PENGARUH PERTUMBUHAN EKONOMI, TINGKAT PENGANGGURAN DAN PENDIDIKAN TERHADAP TINGKAT KEMISKINAN DI ACEH BARAT TAHUN 2014-2024 - Nurhadisah; Fajri Hadi; Mutiara Shifa (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
West Aceh Regency is one of the regions in Aceh Province that faces quite complex poverty challenges. Although this region has abundant natural resources and agricultural potential, its utilization has not been optimal in improving the welfare of the community. The Aceh Province Statistics Agency (BPS) recorded that the percentage of poor people in West Aceh was 17.60%, still above the national average of 9.36% (BPS Aceh, 2024). This means that out of every 100 residents in West Aceh, approximately 18 people still live below the poverty line. The purpose of this study was to determine the impact of economic growth, unemployment rates, and education on poverty in West Aceh in 2014-2024. Based on the results of the research that has been conducted, the results showed that economic growth has no significant and positive effect on poverty in West Aceh Regency. The unemployment rate has no significant and positive effect on poverty in West Aceh Regency. The level of education has a significant and positive effect on poverty in West Aceh Regency. The West Aceh Regency government, as policymakers, is expected to prioritize sectors capable of reducing poverty by improving the quality of education and raising public awareness of its importance.